The Performance of Inflation Forecast Feedback Rules in Small Open Economies - Kai Leitemo (Norges Bank, 2000)
This paper examines the performance of inflation forecast feedback rules in a two-sector, calibrated model of the U.K. economy. Under such rules, the interest rate responds to the deviation of the unchanged-interest-rate forecast of inflation from the inflation target. We find that this procedure may produce a high degree of nominal and real stability, even outperforming the optimal discretionary (flexible) inflation targeting strategy. In order to take adequate account of the exchange rate channel, the feedback horizon will need to be short. A feedback horizon of a year or more creates exchange rate volatility, resulting in higher variability in inflation and traded sector output.
hdl:11250/2500397
Keywords: E61; E47; E43; 330; monetary policy; inflation targeting; inflation feedback rules; simple rules; small open economy